ความชุกชุมและความหลากหลายของแพลงก์ตอนสัตว์กลุ่มเจลาตินัสในอ่าวไทยตอนใน - หัทยา จิตรพัสตร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
A highly diverse group of gelatinous zooplankton plays ecological roles which cover both herbivores and carnivores in marine food chains. Recently, many consequences of gelatinous zooplankton bloom have been concerned and became the global critical problems. The goal of this study was to investigate the abundance and diversity of gelatinous zooplankton in the Inner Gulf of Thailand. Samples of gelatinous zooplankton were collected by a 330µm-mesh net in June and October of 2017 and April 2018 as representatives of southwest monsoon, post-southwest monsoon and summer season, respectively. The total number of gelatinous zooplankton species recorded was 63 with hydromedusae as the most diverse group, while a chaetognath Flaccisagitta enflata was the dominant species in all seasons. However, temporal variation in dominant species was established that F. enflata dominated in both southwest monsoon and summer season, while Doliolum sp. was the dominant species in post-southwest monsoon season. Diversity index of gelatinous zooplankton as well as the density of gelatinous zooplankton from the upper part of the Inner Gulf of Thailand was the highest due to the environment variability especially salinity and the fertility of food sources. The abundance of gelatinous zooplankton also depended on the distance from the river mouth and seasons with the density range of 43-1,369 ind.m-3. Higher abundance was recorded in the upper part and in the summer season. The highest biovolume was noticed during post-southwest monsoon due to the abundance of salps. Community structure of gelatinous zooplankton showed the dissimilarity between the upper part of the Inner Gulf of Thailand and the lower part due to the difference in environmental factors. Hydromedusae dominated in the upper part with low salinity, whereas chaetognaths were the dominant species in the lower part with high salinity values.